Kerja Kalibrasi Pada Geganti Perlindungan (Protection Relay) Dan Penyelenggaraan Pada Pemasangan Elektrik Bagi Industri Kilang Di Johor - Mohd Aslah, Nur Hafizah; mohamed, sulzakimin (Research in Management of Technology and Business, 2022)
In Electrical systems need to be inspected, maintained, replaced and repaired in order to increase the lifespan of the building or components and to prevent any accidents. The capacity of the electrical system that transmits electrical power to certain components should be isolated so as not to expose personnel to explosion, fire, shock or arc explosion (flashover). Safety has priority over service continuity, equipment breakdown, or economy. Inspection is the process of measuring the quality of a product or service to achieve a set standard. In addition, maintenance work involves the coordination of various relevant resources and needs to be managed systematically and effectively. Success or failure in maintenance depends on the effectiveness of the type of maintenance method used. In this regard, in performing maintenance on electrical installations, it is important to know how to perform calibration work on the relay (Protective Relay) and the type of maintenance used in the factory industry in Johor. The objective of this study is to study the implementation method and identify the challenges in implementing the maintenance of the factory industry in Johor. Therefore, the researchers conducted a case study on 5 factories in Johor using the interview method, three of which are palm oil processing plants and two of them are petrochemical plants. The interview consisted of an engineer and a technician and aimed to examine the method of implementation and the type of maintenance adopted. As a result of this research, regular and periodic maintenance are important and able to maintain the function and performance of a component, facility and building. Therefore, it should be wisely implemented accordingly.